Comprehensive Participatory Planning and Evaluation (CPPE) - Pol de Vos; Mayda Guerra; Irma Sosa; Lilian del R Ferrer; Armando Rodríguez; Mariano Bonet; Pierre Lefevre; Patrick Van der Stuyft (Social Medicine Publication Group, 2024)
Participatory Planning and Evaluation (CPPE), an approach to community participation and empowerment developed from the work of Rifkin, LaveracK, Pérez, and others. More than just a methodology, CPPE is an approach which encourages comprehensive analysis and participation by various actors at local, regional, and national level in the planning and evaluation of health actions. CPPE has its roots in the 1980s, when an international team of researchers from the Institutes of Tropical Medicine in Antwerp (ITM-Belgium) and Amsterdam (KIT-Netherlands) developed a framework of comprehensive participatory evaluation for nutritional improvement programs. Following its initial application in the Philippines, further work extended the evaluation approach to planning. CPPE was gradually refined with the support of research teams in Indonesia, the Philippines, and Brazil as they applied it in different contexts and projects. Since 2008 projects have been carried out in Cuba to analyze the possibilities offered by CPPE for increasing community participation in health. This article illustrates the rationale and tools employed in CPPE through our experience in Cuba in the urban municipalities of Centro Habana and Las Tunas and in a rural community in the mountains of Cumanayagua. We discuss key methodological components, the conditions needed for the success of CPPE, and potential differences between the Cuban experience and the possible application of CPPE in other contexts.